Bronzezeitliche Fleischverarbeitung im Salzbergtal bei Hallstatt - Pucher, Erich (Verlag der Österreichischen Akademie der Wissenschaften, 2013)
An animal bone assemblage discovered in an area of Late Bronze Age aboveground activities at the Hallstatt salt mining site was analysed. Together with sunken logwall structurs the results support the idea of a large-scale production of salt-meat, ham and bacon.